Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.2737/nrs-rp-24
|View full text |Cite
|
Sign up to set email alerts
|

Nightly and yearly bat activity before and after white-nose syndrome on the Fernow Experimental Forest in West Virginia

Abstract: In the central Appalachians, conservation concern about bat communities and their population status has become increasingly more significant with the advent and spread of white-nose syndrome (WNS). However, managers often are hampered in their response to WNS by the lack of information on pre-WNS local distribution, abundance, or activity patterns for most bat species. At the Fernow Experimental Forest (FEF), Tucker County, WV, where bat research has been conducted since the mid-1990s, we acoustically monitore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Myotis spp. activity was consistently low over the season relative to summer pre-WNS values [35], only increasing slightly later in the spring, but neither date nor year had a substantial effect on activity level. Myotis spp.…”
Section: Spring Activity Patternsmentioning
confidence: 71%
See 1 more Smart Citation
“…Myotis spp. activity was consistently low over the season relative to summer pre-WNS values [35], only increasing slightly later in the spring, but neither date nor year had a substantial effect on activity level. Myotis spp.…”
Section: Spring Activity Patternsmentioning
confidence: 71%
“…post-WNS and subsequent difficulty in obtaining enough species-specific calls to overcome maximum likelihood estimator identification confidence thresholds [34], along with, known poor echolocation call quality near hibernacula, we grouped all Myotis spp. (MYLE, MYLU, MYSE, and MYSO) as one category [26,35].…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Relative to why burned networks may be more robust against roost loss, the structured nature of roost networks of this species may be in part a response to the ephemeral nature of the roosts used by this species. Unfortunately, WNS appeared within local northern long-eared bat populations in the winter of 2010 and 2011 and precipitous decreases in bat echolocation activity at the FEF were evident by 2012 (Johnson et al 2013). Additional efforts to radio tag and track extant maternity colonies were unsuccessful (Karp 2013) and only one maternity colony on the FEF was documented in the summer of 2013 (J. Rodrigue, USDA Forest Service, Northern Research Station, Princeton, West Virginia, USA, unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…However, with the formerly ubiquitous northern long-eared bat (Myotis septentrionalis Trovessart), now listed as federally threatened in deciduous forests in the East, managers on these forests and elsewhere are now tasked with understanding the response of this species to changes in foraging and day-roosting habitat due to burning. In the central Appalachians, northern long-eared bat foraging activity has been reduced by >75 % (Johnson et al 2013), reflective of the overall regional population declines (Frick et al 2015). Similarly, Francl et al (2012) showed a near cessation of juvenile recruitment from surviving northern long-eared bats in the region following the onset of WNS.…”
Section: Introductionmentioning
confidence: 99%
“…For our case-study, we used a historical data set from the Fernow Experimental Forest (FEF), mostly collected as part of inventory and monitoring work and observational study. The FEF is a small area for which a relatively large and complete data set of acoustic survey data, mist-net capture data, and both maternitycolony and male day-roost data exist for the northern long-eared bat (Ford et al 2006b;Johnson et al 2009Johnson et al , 2010Johnson et al , 2013. Herein, we compare presence-only model results generated from physical capture, acoustic detection, and day-roost locations in a topographically complex, forested landscape.…”
Section: Introductionmentioning
confidence: 99%